Using MDA to Transform Business Processes from Analysis Classes - Boesing, Habner Fabrício; Matos, Simone Nasser; Andrade, Vinicius Camargo; Gueiber, Ezequiel (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2022: Anais do XVI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2022)
This paper proposes a automated transformation method based on the MDA that performs the transformation from the business process diagram (BPMN) to UML classes diagram. This transformation is accomplished through the relationship between the elements of the business process diagram and the class diagram, which generates the transformation rules which are implemented in the Atlas Transformation Language (ATL). This method is intended to standardize the transformation process and decrease the loss of information between the models during the transformation process. Applying the method in three proofs of concept demonstrated that performing a transformation of BPMN to a class diagram is possible.